Blood management in total hip replacement: an analysis of factors associated with allogenic blood transfusion. Issue 6 (17th March 2015) - Wong, Samuel; Tang, Howard; de Steiger, Richard
Abstract Background The aim of this study was to audit the blood transfusion practice throughout the Epworth Healthcare Hospitals for patients undergoing primary total hip replacement (THR). We determined if blood‐saving techniques were having an impact on the risk of allogenic blood transfusion and which patients were at risk of receiving allogenic blood transfusion. Methods This study uses a retrospective audit of 787 patients who had undergone primary THR surgery at three Melbourne hospitals: Epworth Richmond, Epworth Eastern and Epworth Freemasons in 2010. Patient demographics, transfusion requirements and blood‐conserving techniques were recorded. Results One hundred and eighty (23%) patients received allogenic blood transfusion and 18 (2.3%) patients received autologous blood transfusion. On multivariate analysis, preoperative anaemia (odds ratio (OR) 4.7, P < 0.0001), female gender (OR 3.1, P < 0.0001) and patient age (OR 1.07 per year of age increase, P < 0.0001) were shown to be significantly associated with higher risk of allogenic blood transfusion. Use of spinal anaesthetic was found to be associated with lower risk of transfusion (OR 0.6, P = 0.0180) compared with general anaesthetic alone. Cell saver, acute normovolaemic haemodilution and re‐infusion drain tube usage did not have a significant impact on reducing the risk of allogenic blood transfusion. Conclusion Identification of patients at risk of blood transfusion, correction of preoperative anaemia and a restrictive transfusion policy are important factors to consider in effective perioperative blood management.